Impact of the Dren 4000 to the Marine Ecosystem of the Caleta Santa Rosa, Lambayeque and Alternatives of Recovery - Nizama Pacheco, Lizveth Karín (2018)
The objective was to identify the environmental impacts generated by the Drain 4000 of the Caleta Santa Rosa, due to its high contamination as a result of industrial activities; it presents environmental problems that we must solve.The Maximum Permissible Limits for Effluents (LMP), issued by the Ministry of the Environment for domestic and municipal wastewater treatment plants, the Maximum Permissible Limits (LMP) for the fishmeal and fish oil industry, issued by the Ministry were applied. Of the production; and for marine waters, the National Environmental Quality Standards (ECA), giving high levels of pollution. The number of total and thermotolerant coliforms, total suspended solids and BOD5 (Biochemical Oxygen Demand) exceed the maximum permissible limits and the values established in the national environmental quality standards, causing a negative impact on the marine ecosystem. Therefore, it has been proposed recovery alternatives, among the most important: Implementation of a registry of volumes of disembarkation of the resources coming from the operations of the fish processing companies, monthly reports to the General Directorates of Fishing Extraction and Processing and Monitoring, Control and Surveillance, and the proposal of a relocation project of the oxidation lagoon, among others.